Módulos de ensino de comunicação e expressão no ensino supletivo: análise de conteúdo - Motta, Lêda Eulália Cordeiro (1980)
Didatic literature has of late been the object of analysis made to bring out th e ideological meaning of topics that touch the student public. The present work is an addition to those that developed this idea. Its goal is, speeifically, to outline the ideological contents whieh underly the instruments of personalized teaching (Módulos de Ensino) of the Communications and Expression area which are being used in the ' Centros de Estudos Supletivos ' of the State of Rio de Janeiro.